Tajikistan : Programmatic Public Expenditure Review - World Bank (Washington, DC, 2012)
The Programmatic Public Expenditure Review (PPER) has been designed to cover five themes which represent the key challenges for fiscal policy and Public Financial Management System (PFM) reforms in Tajikistan. The themes are as follows: Theme 1: Public Expenditure, Fiscal Space and Growth; Theme 2: Policy-based Budgeting; Theme 3: Efficiency of Public Expenditure in the Social Sectors; Theme 4: Fiduciary Risks; and Theme 5: Inter-governmental fiscal relations. Theme 1 responds to questions of fiscal policy design, especially related to the composition of expenditure and the magnitude of external borrowing, which are becoming increasingly important in Tajikistan and which are likely to have a profound impact on the long term development of the economy. Theme 2 responds to the decision taken by the Government of Tajikistan (GOT) in 2006 to reinvigorate efforts to implement the Medium-term Expenditure Framework (MTEF) and to seek financial and technical support from development partners for this endeavor. Theme 3 focuses on expenditure efficiency in the social sectors, an issue which has not hitherto been subject to rigorous analysis, using methodologies which include efficiency frontier analysis and Public Expenditure Tracking Surveys (PETS). Theme 4 focuses on fiduciary issues and includes a comprehensive evaluation of the PFM system using the internationally accepted best practice methodology of the Public Expenditure and Financial Assessment (PEFA). Theme 5 will provide advice on how the structure of inter-governmental fiscal relations can be reformed to best accommodate the requirements of the MTEF, other PFM reforms and the GOT'S Public Administration Reform Strategy (PARS). This volume of the PPER focuses mainly on Themes 1 and 2, with chapters on how public expenditure can best support economic growth, and on fiscal space for priority expenditures (under Theme 1) and the introduction of the MTEF (Theme 2). It also includes a summary of the PEFA, the main report of which will be published separately.